Papillary Thyroid Carcinoma with Fibromatosis/Fasciitis-Like/Desmoid-Type Stroma: Case Report of a Rare Subtype with Cytological and Molecular Study - Hosamadean Benghashir (22224895) (2024)
Background Papillary thyroid carcinoma (PTC) with fibromatosis/fasciitis-like/desmoid-type stroma is a rare subtype of PTC,characterized by two distinct components: a classic papillary carcinoma component and a spindle cell proliferationresembling fibromatosis or nodular fasciitis. This stromal component adds a unique dimension to the tumor'spathology, making diagnosis more challenging and potentially leading to misclassification. Case presentation We present a case of this rare entity which contributes to the growing body of literature by providing additionalmolecular data, which may shed light on the biological behaviour of the fibromatosis-like stroma and its relationshipwith the papillary carcinoma component. This case underscores the importance of recognizing this subtype, as itsspindle cell proliferation could be mistaken for a separate neoplasm or reactive process, resulting in inappropriatemanagement. Conclusions Increased awareness of this entity will help pathologists avoid diagnostic pitfalls and guide clinicians in developingmore precise treatment plans, addressing both the malignant papillary component and the unique stromal features.This case further enriches the current understanding of the heterogeneity of PTC and highlights the need fortailored management strategies in rare subtypes. Other Information Published in: Head and Neck Pathology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12105-024-01720-8